Clinical presentation of a pilocytic astrocytoma concomitant with hydranencephaly: First case reported in Colombia: Pilocytic astrocytoma concomitant with hydranencephaly: First case reported in Colombia - Serna-Trejos, Juan Santiago (2024)
ABSTRACT Pilocytic astrocytoma is a glioma-like neoplasm, slow growing and with little risk of tumor progression. Its course with hydranencephaly is not described to our knowledge in the Colombian literature. We describe the case of a pediatric patient with the presence of convulsive neurological symptoms with a history of tuberous sclerosis which will be a key determinant in the relationship between the relationship between astrocytoma preceded by hydranencephaly, since they include genetic aberrant mechanisms for the development of the latter. The clinical outcome of the patient was purely palliative. Keywords: Astrocytoma; Juvenile Pilocytic Astrocytoma; Pilocytic Astrocytoma; Hydranencephaly; Hemihydranencephalies; Congenital Absence of Cerebral Hemispheres